Contribution of Primary Pelvic Organ Prolapse to Micturition and Defecation Symptoms. (29th September 2011) - Groenendijk, Annette G.; Birnie, Erwin; Roovers, Jan-Paul W.; Bonsel, Gouke J.
Abstract : Objective . To investigate the contribution of Pelvic Organ Prolapse (POP) to micturition and defecation symptoms. Method . Cross-sectional study including 64 women presenting with POP symptoms and 50 controls without POP complaints. Subjects were evaluated using POP-Quantification system, Urinary Distress Inventory, and Defecation Distress Inventory. The MOS SF-36 health survey and the Center for Epidemiological Studies Depression scale were used to measure self-perceived health status and depressive symptoms, respectively. Results . POP in terms of POP-Q had a moderate impact on the symptom observing vaginal protrusion (explained variance 0.31). It contributed modestly to obstructive voiding and overactive bladder symptoms (explained variance 0.09, resp., 0.14) but not to urinary incontinence. Constipation was more likely explained by clinical depression than by pelvic floor defects (explained variance 0.13, resp., 0.05). Conclusion . Stage of POP and specific prolapse symptoms are associated but such a strong association does not exist between POP and micturition or defecation symptoms.